The Influence of the Combination of Acupressure on the Meridian Point P6 and Peppermint Aromatherapy Inhalation on the Reduction of Nausea and Vomiting Frequency in First-Trimester Pregnant Women - Sari, Atika Kurnia; Setianingsih, Setianingsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Nausea and vomiting disorders during pregnancy, particularly in the first trimester, often impact the quality of life for pregnant women, with 50-90% of cases occurring during this period. Besides affecting maternal health, these disorders also influence fetal growth and development. Management can be achieved through pharmacological and non-pharmacological methods, including the combination of acupressure at Meridian Point P6 and inhalation of peppermint aromatherapy.This research aims to evaluate the impact of this combination on reducing the frequency of nausea and vomiting in first-trimester pregnant women at RSHM Yusuf Kalibalangan in North Lampung. Utilizing a quasi-experimental method, involving 12 first-trimester pregnant women experiencing nausea and vomiting at the mentioned hospital, the study results demonstrate that the combination of acupressure and peppermint aromatherapy significantly reduces the frequency of these symptoms. Statistical analysis using the paired t-test yields a p-value of 0.012. In conclusion, this combination proves effective in addressing nausea and vomiting issues in first-trimester pregnant women at RSHM Yusuf Kalibalangan in North Lampung, offering new insights into non-pharmacological options for improving the well-being of pregnant women.